Sorption of oxadiazon in soils cultivated in the brazilian cerrado - Mendes, K.F.; Reis, M.R.; Pereira, A.A.; Nunes, A.R.S.; Santos, C.E.M.; Assis, A.C.L.P. (Planta Daninha, 2013)
The objective of this study was to evaluate oxadiazon sorption in different soils of the Brazilian Cerrado, highlighting the correlations of lethal doses of this herbicide capable of inhibiting 50% of the dry matter accumulation of the bio-indicator (LD50) among the chemical characteristics of the soil and its direct and indirect effects. The experiment was carried out in a greenhouse in a randomized block design and four repetitions. Each experimental unit consisted of a pot with increasing rates of oxadiazon and oat (Avena sativa), as the bio-indicator species. For sorption evaluation, washed sand and 22 soils (substrates) from Cerrado Brazilian's Alliaceae cultivated areas were used. LD50 and sorption ratio (SR) = [(LD50soil - LD50sand)/LD50sand] to the substrates were determined. Pearson correlation analysis was performed between the chemical characteristics of the substrates and the LD50 of oxadiazon. A path analysis was quantified, to deploy only the significant correlations estimated in direct and indirect effects of the characters on LD50, which is a basic variable. A more pronounced LD50 (528.09 g ha-1) for the Cerrado soil sample resulted in higher SR (> 53.00), while in the washed sand substrate, LD50 corresponded only to 9.74 g ha-1 of the oxadiazon (available in soil). It was concluded that oxadiazon sorption is influenced by the chemical characteristics of the soils, highlighting the correlation with pH (CaCl2), magnesium content, aluminum, organic matter, organic carbon, and aluminum saturation.

Objetivou-se neste estudo avaliar a sorção do oxadiazon em diferentes solos do Cerrado Brasileiro, destacando as correlações da dose letal do herbicida capaz de inibir 50% do acúmulo da massa seca do bioindicador (DL50) entre as características químicas do solo e seus efeitos diretos e indiretos. O experimento foi realizado em casa de vegetação, com delineamento em blocos casualizados com quatro repetições. Cada unidade experimental foi constituída de um vaso com doses crescentes do oxadiazon; utilizou-se a aveia (Avena sativa) como espécie bioindicadora. Na avaliação da sorção, foram utilizados areia lavada e 22 solos (substratos) provenientes de áreas cultivadas com Alliaceae no cerrado Brasileiro. Foram determinadas a DL50 e a relação de sorção (RS) = [(DL50solo - DL50areia)/DL50areia], para os substratos. Posteriormente, análise de correlação de Pearson foi realizada entre as características químicas dos substratos e a DL50 do oxadiazon. Foi quantificada ainda a análise de trilha, a fim de desdobrar somente as correlações significativas estimadas em efeitos diretos e indiretos de caracteres sobre a DL50, que é uma variável básica. A DL50 mais expressiva (528,09 g ha-1) para uma das amostras de solo de cerrado resultou em maior RS (> 53,00). Já no substrato de areia lavada, a DL50 foi de apenas 9,74 g ha-1 do oxadiazon (disponível no solo). Conclui-se que a sorção do oxadiazon é influenciada pelas características químicas dos solos, ressaltando a correlação com o pH (CaCl2), teor de magnésio, alumínio, matéria orgânica, carbono orgânico e a saturação por alumínio.
Keywords: Bioensaio; Herbicida neutro; Matéria orgânica